A Case of Familial Mediterranean Fever After Renal Transplantation: From Phenotype II to I - Yalçın SOLAK,; Hüseyin ATALAY,; İlker POLAT,; Zeynep BIYIK,; Abduzhappar GAIPOV,; Adem KÜÇÜK,; Süleyman TÜRK1, (Archives of Rheumatology, 2012)
Familial Mediterranean fever (FMF) is the prototype of autoinflammatory syndromes. Several factors may trigger the disease including physical and emotional stress, fatrich diet, and menstruel cycle. Infections and some drugs such as cisplatin may result in a change in cytokine levels and may precipitate attacks. Most cases of FMF presents with typical self-limited attacks including fever and abdominal pain. However, a minority of patients, called as phenotype II, presents with amyloidosis AA-type and/or end-stage renal disease in the absence of clinically recognizable attacks. Immunosupression may precipitate a typical FMF attack, possibly through a change in cytokine balance. Initiation of colchicine treatment in these patients is of utmost importance to prevent amyloidosis involvement of the newly transplanted graft. In this article, we present a rare case of FMF who transformed from phenotype II to phenotype I after renal transplantation, most probably due to the effect of immunosuppressants.